Carboxymethyl chitosan/inulin composite films incorporated with different phenolic compounds as a potential new material for food packaging applications - Ulu, Oznur Dogan; Ulu, Ahmet; Birhanli, Emre; Pekdemir, Mustafa Ersin; Ates, Burhan (Elsevier, 2026)
In this study, three types of biodegradable packaging composite films were developed using a solution casting method for the packaging of food products: Composite films based on carboxymethyl chitosan (CMCS) linked with inulin (INU) and then combined with gallic acid (GA), tannic acid (TA), and naringenin (NAR). The swelling capacity and water vapor permeability of the composite films increased by 3.5-fold compared to the CMCS/INU film, while the moisture content remained almost unchanged. Additionally, the results showed that the incorporation of phenolic compounds significantly improved the UV resistance of composite films, and the UV shielding rate of all composite films reached to 95-99 %. Crucially, the incorporation of phenolic compounds imparted excellent antimicrobial properties as well as remarkable antioxidant activity with over 90 % free radical scavenging rate. While the CMCS/INU film did not show inhibition zone diameter against P. aeruginosa, S. aureus, and C. albicans, the inhibitory zone diameters of the CMCS/INU/TA composite film were found to be 19.75, 22, and 18 mm, respectively. Most importantly, shelf life of green grapes and chicken meat packaged in composite films was effectively extended from 3 days to 12 and 7 days without any decay, respectively. Considering this fact, this study not only provides valuable insights into the development of films with antioxidant and antimicrobial properties but also provides a promising framework for advancing active food packaging technologies.
Keywords: Carboxymethyl chitosan; Inulin; Phenolic compounds; Composite film; Food packaging